GM trust shaped by trust determinants with the impact of risk/benefit framework: the contingent role of food technology neophobia. Issue 1 (2nd January 2021) - Ali, Sumran; Nawaz, Muhammad Asim; Ghufran, Muhammad; Hussain, Sumaira Nazar; Hussein Mohammed, Aljaifi Saddam
ABSTRACT: The present study is comparative in natures that focus on understanding the factors that influence the GM food trust level in the BRA framework and food technology neophobia in China and the USA. For this purpose, we collected 300 and 350 valid responses, respectively, through a structured questionnaire. By carefully evaluating the above relationships, we found that trust determinants such as institutional trust, technology trust, information revealed with GM food vary across both datasets. However, GM knowledge has a better association with GM food trust in both cases. Apart from this, the food technology neophobia slightly moderates the benefits-risk perception of consumers and GM trust. This study guides the policymakers to enhance GM knowledge, as GM food is scientifically proven safe for health and environment and can be a financial incentive for the farmers. Further, the study also provides direction for corporate managers to design effective marketing and communication strategies in two different countries by investigating GM food trust's primary motivators in both nations.